Substituted Apatite/Poly-Epsiloncaprolactone Biocomposite As Substrates And Coating On Alphatricalcium Phosphate Foams - Lee, Thi Bang (2013)

(untitled)
In this research, carbonate and silicon-substituted apatite/poly-ɛ-caprolactone biocomposite were produced to be used as a porous biocomposite bone substitute. Carbonate apatite/poly-ɛ-caproplactone (CO3Ap/PCL) was also used to coat on a fully interconnected structure of α-tricalcium phosphate (α-TCP) foam to enhance the mechanical and biological properties, and to mimic the structure of cancellous bone. Carbonate apatite (CO3Ap) and silicon-substituted carbonate apatite (Si-CO3Ap) were synthesized by a precipitation method. The results revealed that the silicate and carbonate ions competed to occupy the phosphate site and also entered simultaneously into the hydroxyapatite structure. The Si-substituted CO3Ap reduced the powder crystallinity and promoted ion release which resulted in a better solubility compared to that of Si-free CO3Ap. The silicon and carbonate co-substitution appeared to have a better effect on the early stages of osteoblast behavior (cell attachment and proliferation) rather than the immediate/late stages (proliferation and differentiation). The fabrication of a biocomposite derived from an interconnected porous Si-CO3Ap reinforced with molten poly-ε-caprolactone (PCL) was then developed to mimic the composition and structure of bone coupled with enhanced mechanical performance. Porous silicon-substituted carbonate apatite blocks were produced using wax as a volatile agent. The interconnected porous Si-CO3Ap obtained has a porosity of about 80% and a pore size of about 100-200 μm. The PCL covered, and penetrated into the pores of, the porous Si-CO3Ap to form an excellent bonding with Si-CO3Ap leading to a significant increase in diametral tensile strength xxi from 0.23 MPa to a maximum of 2.04 MPa. However, although the porous biocomposite meets the requirement of biological bone to some extent, it remains a great challenge to make the ideal bone substitute materials that mimic the natural structures, in which, a fully interconnected structure should be highly considered. The mechanical behavior, microstructure and cell responses of CO3Ap/ PCL coated α-tricalcium phosphate (α-TCP) foams were studied as an initial step for the fabrication of a cancellous-type artificial bone replacement. The α-TCP foam was obtained by sintering CaCO3 and CaHPO4•2H2O at 1500oC. It was then coated with CO3Ap/PCL and its three dimensional, fully-interconnected porous structure was found to be maintained. CO3Ap/PCL coating on α-TCP foam was proven to be very effective in increasing the mechanical strength by 25 times and toughening the α- TCP foam, in addition to excellent biocompatibility as proven by bone marrow cell studies. The coated α-TCP specimens exhibited high porosity (80-85%) with large pore size (500-700μm) that mimic the cancellous bone structure. The in vitro biological evaluations indicated that CO3Ap/PCL used for coating improved cellular attachment, accelerated proliferation and resulting in a greater alkaline phosphatase (ALP) activity of both MC3T3-E1 cell-like and rat bone marrow cells.